Trends of nitrogen use of oat cultivars from 1902 to 2002 in Finland - Muurinen, Susanna; Peltonen-Sainio, Pirjo (MTT, 2004)
Plant breeding has improved grain yields of oats in northern growing conditions (Rekunen 1988, Slafer &Peltonen-Sainio 2001).One main contributor to increased yields is harvest index (HI). Cultivars have higher HI and reduced plant height compared to landraces or old cultivars (Peltonen-Sainio 1991). The response of oats to nitrogen fertilizers is also improved (Peltonen-Sainio 1993). The aim of this study was to identify the changes in nitrogen economy caused by plant breeding in northern growing conditions. In growing season 2003, eighteen oat cultivars (released between 1902 and 2002) were studied in MTT, Jokioinen. Experiment was treated with 70 kg N ha-1 and soil N content was measured on spring and autumn. Plant samples were collected at maturity and the plants were divided into main shoots and tillers and further to panicles and vegetative mass. The dry weight was measured and samples were grind for N analyses. Nitrogen harvest index (NHI), N utilization efficiency (UTE), N uptake and N use efficiency were calculated from the dry weights and N contents of the plants. On the basis of one year results, plant breeding has only changed the N utilization efficiency, not so much N uptake. There were no significant difference between the cultivars in N use efficiency or in N content of the plant (g N m- 2). Cultivars did not differ in N uptake either. Instead UTE on new cultivars was 38.4 g g N-1 while it was 35.1 g g N-1 on old cultivars. There was positive correlation between UTE and NHI and also between NHI and HI. The one year results imply that grain yield is more breed quality than N content or N uptake. Peltonen-Sainio, P. 1991. Journal of Agronomy & Crop Science 166: 90-95; Peltonen-Sainio, P. 1993. Journal of Agronomy & Crop Science 171: 268- 273; Rekunen, M. 1988. Journal of Agricultural Science in Finland 60: 307- 321; Slafer, G. & Peltonen-Sainio, P. 2001. Agricultural and Food Science in Finland 10: 121-131.
Keywords: Ka; typen käyttö; NUE; satoindeksi; typpisatoindeksi; kaura; jalostus; lajike; typpi; lannoitus; radiation use efficiency light; extinction coefficient